A multifunctional ingredient for the management of metabolic syndrome in cafeteria diet-fed rats. Issue 2 (5th January 2021) - Martín-González, Miguel Z.; Palacios-Jordan, Héctor; Mas-Capdevila, Anna; Rodríguez, Miguel A.; Bravo, Francisca I.; Muguerza, Begoña; Aragonès, Gerard
Abstract : A novel dietary multifunctional ingredient improves glucose and lipid homeostasis and exhibits antihypertensive properties in cafeteria-fed obese rats. Abstract : The body weight-lowering properties of a multifunctional ingredient (MIX) based on conjugated linoleic acid at low doses, the flavonoids proanthocyanidins and anthocyanidins and the chicken feet hydrolysate Hpp11 have been previously reported. The aim of this study was to evaluate the effect of long-term administration of MIX on other cardiometabolic risk factors associated with metabolic syndrome (MetS) in rats fed a cafeteria diet (CAF). Male Wistar rats were fed CAF for 11 weeks, and during the last 3 weeks, animals were orally administered MIX or vehicle. Lipid tolerance tests were performed before and after MIX administration. At the end of the experimental period, serum and inguinal white adipose tissue (iWAT) metabolism were analyzed by metabolomics and biochemical approaches. The metabolite signature of serum and iWAT significantly changed after 3 weeks of MIX administration, suggesting an improvement in lipid and glucose homeostasis in these animals. In addition, MIX also exhibited significant antihypertensive properties. These results suggest that MIX could be a good candidate to ameliorate the cardiometabolic risk factors related to MetS.